Flexible self-locking intermodular connection for prefabricated modular steel buildings - Gohar, Nadeem (2022)
The modular building uses factory-built 3D or room-sized volumetric modules. They assemble on site as the building's key structural elements. Compared to conventional construction, modular constructions are different in detailing requirements, construction method, structural performance, and load-transfer mechanism. In conventional steel structures, the structural members have a high degree of connectivity, whereas in modular construction, the modules are connected at their corners only by inter-modular connections (IMC), and these connections are the most vulnerable points of failure. In the connecting region, numerous small beams and columns meet together, which poses new challenges to structural design. Currently, the inter-modular connections are pinned connections, which are provided in the form of a connection plate and a high-strength bolt. An access hole in the column is provided for the erection of the bolt, which causes cross-sectional loss of the column and is unfavorable for the “strong column-weak beam” seismic design concept, leading to unfavorable failure mechanisms which can threaten the entire structure. This study proposed a self-locking connection to address these issues of IMCs. The proposed connection uses a simple mechanism of spring to be fixed, does not require extra workspace between modules, and is suitable for interior, exterior, and corner joints. Proposed connection comprises of upper and lower adapters, flat spring, spring pin, center plate and middle plate the center plate and adapter are welded together; the flat spring is free at the one end to move, while it is fixed through welding at other end. The adjacent module in internal as well as exterior joint are connected by middle plate. The middle plate is positioned on top of the upper adaptor, the upper adaptors are inserted through square spaces providing on middle plates. Dowel pins are provided at each corner of the center plate to allow for the alignment of the modules that are joined to the middle plate during assembly. The distance between floors beam as well as the ceiling beam is similar as total thickness of middle plates and the center plate. This interconnection will transfer the primary failure locations away from important structural parts like columns and provide adequate seismic load stress mitigation. The connection components can be fabricated off-site and assembled on-site. Finally, this would result in a multistory modular building structure entirely manufactured off-site and assembled as a full-frame capable of withstanding gravity and lateral loading. Experimental tests were performed to verify and analyze the strength and the predicted ductile failure pattern of the newly proposed inter-modular connections. The details of the test specimens were selected based on a six-story modular residential building design; a height of 3m and width of 3.6m of the module was considered. T- shaped specimens were fabricated to simulate the corner joint of MSB; half of the original height and width of a module was adopted presuming that beam and column inflection points coincide at the center length of the member. Under monotonic and cyclic load, three full-scaled specimens were tested to compare the joints' mechanical behaviour. Extensive numerical studies were carried out utilizing established methodologies for finite element modeling to investigate and compare the proposed connections in terms of seismic response and slip mechanisms with those of a standard inter-modular connection currently used in steel modular buildings. Finite element models were discretized by employing the appropriate mesh elements. Due to the higher accuracy, all parts were modelled with brick elements (hexahedral) For steel modelling a nonlinear steel behavior signified by bi-linear stressstrain relationship was considered. Furthermore, the surface-Surface technique was employed to define property between bolt shank, bolt hole and surfaces of the plates. Parametric sensitivity analyses were conducted to determine the parameters and the components that influence the performance and failure mechanisms of the proposed connection. The experimental and finite element analyses show that the proposed intermodular connections have better seismic behavior across a range of response characteristics, including moment-carrying capacity, energy dissipation capacity, and ductility. The ductile failure patterns were observed among beams, with no severe plastic deformations in critical structural components like columns or joints. The findings provide ideas for the design and analysis of intermodular connections that meet the requirements of entirely modular buildings. This research will lead to considerable improvements in the dynamic response and life safety of modular structures subjected to lateral loads in general and seismic loads in particular.